Diagnostic Investigations as a Basis for Optimising Surgical Management of Vertebrobasilar Insufficiency Syndrome - Chmutin, Gennady; Antonov, Gennady; Chmutin, Egor; Fedyanin, Aleksei; Livshitz, Matvey; Oleynikov, Boris; Zokhidov, Zokirzhon; Shumadalova, Alina (Frontiers in Surgery, 2022)
Vertebrobasilar insufficiency (VBI) is one of the most common forms of cerebrovascular pathology. The progression of the VBI, especially in the context of inadequate therapy, often leads to the formation of a persistent neurological deficit within the framework of dyscirculatory encephalopathy and the consequences of a stroke in the vertebrobasilar system. This study demonstrate the importance of objective methods of patient investigation to optimize the choice of the most effective methods of surgical treatment for VBI in cases of ineffective medical treatment. We have shown that the optimization of the diagnostic algorithm contributes to the correct individualized determination of types of surgical treatment for patients with VBI. Was found that, in addition to traditional diagnostic methods, the use of radiographic methods (ultrasound Doppler, multispiral computed tomography with contrast enhancement) is invaluable for choosing the tactics of surgical treatment. We propose a significant outcome indicator like the blood flow reactivity index to determine the postoperative improvement of blood flow in the vertebral arteries. In addition, the need to perform cerebral angiography and consultations with related specialists to exclude pathologies with a similar clinical picture is emphasized